An Exploration of Corporate Social Responsibility Initiatives in Bangladesh's Private Commercial Banks - Rahman , Md. Khalilur; Badsha, Rahim; Darda, Md. Abud (Business Management and Strategy, 2024)
This study examined the corporate social responsibility (CSR) initiatives of 18 listed private commercial banks in Bangladesh from 2013 to 2019. Data were collected from annual reports and analyzed using descriptive statistics and Pearson’s correlation. The results indicated that Bangladeshi private commercial banks primarily focus on eight CSR areas, with disaster management being the most significant contributing factor. Islami Bank Bangladesh emerged as the highest CSR contributor, whereas Uttara Bank and Eastern Bank were the lowest. A significantly positive relationship was found between the amount of CSR contribution and bank size. However, higher profitability did not necessarily correlate with increased CSR activities. This research enhances understanding of CSR practices in Bangladeshi commercial banks and provides recommendations for potential avenues for future studies, such as the impact of CSR activities on beneficiaries' lives.